2024
DOI: 10.1001/jamaophthalmol.2024.0017
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of an Artificial Intelligence Chatbot’s Interpretation of Clinical Ophthalmic Images

Andrew Mihalache,
Ryan S. Huang,
Marko M. Popovic
et al.

Abstract: ImportanceOphthalmology is reliant on effective interpretation of multimodal imaging to ensure diagnostic accuracy. The new ability of ChatGPT-4 (OpenAI) to interpret ophthalmic images has not yet been explored.ObjectiveTo evaluate the performance of the novel release of an artificial intelligence chatbot that is capable of processing imaging data.Design, Setting, and ParticipantsThis cross-sectional study used a publicly available dataset of ophthalmic cases from OCTCases, a medical education platform based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…These findings, along with those from the study by Mihalache et al, illustrate the current limitations of LLMs in the interpretation of medical imaging studies, indicating a substantial gap between its potential and current capabilities in medical diagnostics. While these AI models hold promise for revolutionizing various aspects of clinical practice, their accuracy in image-based diagnostics is currently limited by their inherent design for visual data processing.…”
supporting
confidence: 52%
See 1 more Smart Citation
“…These findings, along with those from the study by Mihalache et al, illustrate the current limitations of LLMs in the interpretation of medical imaging studies, indicating a substantial gap between its potential and current capabilities in medical diagnostics. While these AI models hold promise for revolutionizing various aspects of clinical practice, their accuracy in image-based diagnostics is currently limited by their inherent design for visual data processing.…”
supporting
confidence: 52%
“…To the Editor We read with interest the article “Accuracy of an Artificial Intelligence Chatbot’s Interpretation of Clinical Ophthalmic Images” by Mihalache et al in which the authors continued their exploration into the utility of ChatGPT-4 (OpenAI), an advanced artificial intelligence (AI) chatbot, in ophthalmology . Their latest study critically evaluated the ability of this chatbot to answer multiple-choice questions in ophthalmology, focusing on its performance in interpreting ophthalmic images.…”
mentioning
confidence: 99%
“…The significantly higher accuracy (70%) achieved by Mihalache A et al using GPT-4V on OCT images might be attributed to their use of multiple-choice questions, while our study used open-ended questions. [22]…”
Section: Discussionmentioning
confidence: 99%
“…In Reply We sincerely thank Koga and Du for their comments on our article . As discussed by Koga and Du, we note that large language models, such as ChatGPT (OpenAI), are currently limited in the domain of ophthalmic imaging interpretation.…”
mentioning
confidence: 99%
“…As discussed by Koga and Du, we note that large language models, such as ChatGPT (OpenAI), are currently limited in the domain of ophthalmic imaging interpretation. Our recent investigation found that the chatbot underperformed on image-based questions compared with questions that did not directly require ophthalmic imaging interpretation . As per the ChatGPT-4V(ision) system card, OpenAI notes that the chatbot’s imaging interpretation features are unsuitable for carrying out any medical function.…”
mentioning
confidence: 99%